P38 siRNA-encapsulated PLGA nanoparticles alleviate neuropathic pain behavior in rats by inhibiting microglia activation. (20th July 2018) - Shin, Juhee; Yin, Yuhua; Park, Hyewon; Park, Seungjo; Triantafillu, Ursula L; Kim, Yonghyun; Kim, Sang Ryong; Lee, Sun Yeul; Kim, Do Kyung; Hong, Jinpyo; Kim, Dong Woon
Aim: To investigate whether p38 small-interfering RNA-loaded nanoparticles (p38 siRNA NPs) attenuate spinal nerve ligation (SNL)-induced neuropathic pain in rats by suppressing spinal microglia activation via p38 targeting.Materials & methods: After synthesizing p38 siRNA NPs with sonication, physical characteristics were measured for size and zeta potential. p38 siRNA NPs were then administrated intrathecally into SNL rats if they could reduce pain behavior excellently.Results: p38 siRNA NPs significantly reduced mechanical allodynia as well as microgliosis in the spinal dorsal horns of SNL rats, consistent with a downregulation of p38-related proinflammatory mediators.Conclusion: As p38 in the spinal microglia plays a critical role in neuropathic pain, we expect that p38 siRNA NPs could be a promising tool for the treatment of neuropathic pain.